Dynamic Response of Historical Masonry Minaret under Seismic Excitation - Takwa A. Khider; Hayder A. Al-Baghdadi (Civil Engineering Journal, 2020)
In order to study the dynamic response of historical masonry structures, a scaled down brick masonry model constructed in civil engineering department at Baghdad University to simulate a part of a real case study, which is Alkifil historic minaret. Most of the previous researches about masonry structures try to understand the behavior of the masonry under seismic loading by experimental and numerical methods. In this paper, the masonry units (bricks) simulated in scale (S= 1/6) with the exact shape of the prototype bricks. Cementitious tile adhesive was selected to be the mortar for the modeling. The height of the model designed to be 1.5 m with a 0.5 m diameter. Detailed construction steps were presented in this paper. Experts built the model with high accuracy. A shaking table and other dynamic testing facilities were used at the University of Baghdad. The model was tested using the time-compressed El Centro 1940 NS earthquake at different amplitudes. The first ground motion of (PGA= 0.05g) which considered as weak ground motion was used to check the adequacy of the conventional behavior of the masonry model and the limit of the elastic behavior of the model during weak earthquakes. Moderate ground motion (PGA=0.15g) was performed to investigate the response of the model with minor to moderate damages. The severe ground motions were not appropriate to use in such circumstances because of the possibility to overturn the model. The experimental results showed very adequacy of the model to withstand the weak and moderate earth motion with no observed cracks.